The relationships between depression and complications in diabetes mellitus - Makara-Studzińska, Marta; Partyka, Iwona; Ziemecki, Piotr; Ziemecka, Anna; Andrzejewska, Dorota (Current Problems of Psychiatry, 2013)
Comorbid depression is associated with complications in diabetes mellitus.The aim of this study is to review the literature on the relationship between the occurrence of depression and the presence of complications in diabetes.PubMed database was searched for depression in diabetes mellitus type 1 and 2 with all kinds of complica-tions in adults to identify relevant studies published between 2000 and 2012 mostly available in English.There is a statistically significant association between depression and complications in diabetes mellitus.Additional studies are needed to clarify the underlying mechanisms for this association, temporal relationships and to analyze the association between depression and particular type of complication. Further research to investigate emotional problems other than mood disorders is needed.